1991
DOI: 10.1111/j.1533-8525.1991.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Crime in Urban Residential Neighborhoods: Implications of Between- and Within-Neighborhood Sources for Current Models

Abstract: Current work on fear of crime centers largely around three dominant theoretical models: indirect victimization, community concern, and incivilities. Previous work (Taylor and Hale 1986) confirms the importance of the central construct in each model and shows that no one model has more explanatory power than another. But work to date has not examined ecological impacts of some key constructs, even though the models clearly imply processes operative at the neighborhood level. This study extends earlier work, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
335
5
26

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(401 citation statements)
references
References 20 publications
30
335
5
26
Order By: Relevance
“…An exception to the lack of independent observations of disorder at the level of ecological units rather than persons is found in research by Taylor and colleagues (Taylor, Shumaker, and Gottfredson 1985;Taylor, Gottfredson, and Brower 1984;Covington and Taylor 1991;Perkins et al 1992;Perkins and Taylor 1996; see also Mazerolle, Kadleck, and Roehl 1998). 5 Using observations conducted by teams of trained raters walking the streets, Taylor et al (1985) assessed 20% of all occupied face blocks in 66 Baltimore neighborhoods.…”
Section: Systematic Social Observation Of Disordermentioning
confidence: 99%
“…An exception to the lack of independent observations of disorder at the level of ecological units rather than persons is found in research by Taylor and colleagues (Taylor, Shumaker, and Gottfredson 1985;Taylor, Gottfredson, and Brower 1984;Covington and Taylor 1991;Perkins et al 1992;Perkins and Taylor 1996; see also Mazerolle, Kadleck, and Roehl 1998). 5 Using observations conducted by teams of trained raters walking the streets, Taylor et al (1985) assessed 20% of all occupied face blocks in 66 Baltimore neighborhoods.…”
Section: Systematic Social Observation Of Disordermentioning
confidence: 99%
“…Variation in self-reported levels of FOC generally do not reflect local crime rates, particularly when individual-level factors such as social class are controlled for (DuBow, McCabe, & Kaplin, 1979;Taylor & Hale, 1986;Taylor & Shumaker, 1990). Research has shown that levels of FOC are in fact inversely related to real-world estimates of victimization risk (Akers, La Greca, Sellers, & Cochran, 1987;Covington & Taylor 1991;Lebowitz, 1975;Yin, 1980Yin, , 1985. This phenomenon, often referred to as the paradox of fear, has been the subject of much research.…”
Section: Fear Of Crime As a Key Environmental Determinant Of Mental Hmentioning
confidence: 99%
“…Incivilities, or physical signs of social disorder such as litter, graffiti, and abandoned buildings, have been shown to correlate with local FOC (Covington & Taylor, 1991;R. B. Taylor & Covington, 1993;Sampson & Raudenbush, 2004).…”
Section: Fear Of Crime As a Key Environmental Determinant Of Mental Hmentioning
confidence: 99%
“…Ancak bu yaklaşım ile ilgili bilimsel çalışmalar çoğunlukla Amerika Birleşik Devletleri'nde yaşayan insanlar esas alınarak yapıldığı için kültür, ırk, etnik yapı gibi tabirlerin başka toplumlar için daha başka anlamlar ihtiva edebileceği, aynı anlamları ihtiva etse bile suç korkusu üzerindeki etkilerinin çok daha farklı olabileceği akıldan çıkarılmamalıdır (Covington/ Taylor, 1991).…”
Section: Sosyal Kontrol Perspektifiunclassified